Groundwater resources in an alluvial aquifer in the Northeastern semi-arid region: a case study in the Morada Nova Irrigation Project, CE (Research, Society and Development, 2023)
The irregular rainfall and the years of low rainfall are important factors that lead farmers in the semi-arid region to seek alternatives that enable the continuity of production activities. The objective of the study was to analyse the behaviour of wells in the semi-arid region, in the Morada Nova Irrigation Project, located in the municipalities of Morada Nova and Limoeiro do Norte - CE. Monthly readings of static level of the wells during the years 2014 to 2019 were considered. The static level data were treated and organized in graphs and iso-depth maps to enable the observation of the water table behavior during dry and rainy seasons. The rise and depletion of each well over the year was analysed using the use and recovery coefficient. The graphs and maps showed a large drop in the static levels of the wells mainly in the year 2015 and recovery of the levels in the year 2018, the best year of rainfall; extending the recovery until 2019. The use and recovery coefficient made it possible to estimate how much was exploited of the wells during each year, highlighting the year 2015 with the highest depletion of the wells, with an average of 3.26 m, and the year 2016, with the coefficient value of 12.95.  The year 2018 obtained the best coefficient, with the value of 0.58, and the average rise of the wells of 2.18 m. Such favorable indices are justified by the occurrence of rainfall above the historical average in the region, confirming strong collaboration and interference in the rainy and dry seasons.